Teachers’ Experiences in Evaluating Learning Process: A Case Study of Online Learning - Reli Handayani; Saharudin Saharudin; Ady Muhammad Zainul Mustopa; Sonya Trikandi (Universitas Batanghari Jambi, 2022)
Evaluation of learning is a crucial step in understanding the progress of students' competence and determining the success of the learning process. This study aims to explain, with reference to the 2013 Curriculum, the experience of teachers conducting evaluations during online learning. This study focused on nine English teachers from nine public schools in Jambi City, including five junior high schools, two high schools, and two vocational high schools. This case study employed an interview instrument which data were then qualitatively analyzed. The findings of this study include teachers' comprehension of learning evaluation, forms of assessment, barriers in the learning process, and the effectiveness of implementing learning evaluation. First, teachers have a comprehensive understanding of learning evaluation, which includes students’ knowledge, skills, and attitudes. However, teachers consider the number of student competencies that must be assessed in online learning to be burdensome, specifically due to limited hour of meeting. The teachers emphasize on delivering the material and decrease the number of competencies that students must acquire. Second, teachers assign daily tasks to assess students' knowledge, video projects to assess their skills, and pay attention to the punctuality of assignment submission and classroom interaction to assess students' attitudes. Third, the obstacles of learning include the absence of gadgets, limited of internet quotas, the difficulty of the internet access, the lack of student participation, and the absence of parental support for online learning. Fourth, the limited abilities of teachers, the difficult conditions of students, and the limited time contribute to the ineffectiveness of the online learning process. In conclusion, the evaluation of online learning cannot completely reference the curriculum.